2022
DOI: 10.1002/slct.202103234
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Materials Developed from Nano‐hydroxyapatite Impregnated Chitosan/κ‐Carrageenan for Bone Tissue Engineering.

Abstract: Herein, nano-hydroxyapatite impregnated chitosan/k-carrageenan (nHAp/CHI/k-CGN) nanocomposite was prepared through co-precipitation approach and was compared with nano-hydroxyapatite/chitosan (nHAp/CHI) nanocomposite for bone regeneration capability. The comparative assessment carried out through Scanning electron microscopy, Fourier transform infra-red spectroscopy, X-ray diffraction and mechanical testing revealed rough surface morphology, better interaction between the components, favorable crystallinity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Furthermore, the PHBV NPs‐CGN‐HA hydrogel showed higher efficiency in terms of promoting MG‐63 proliferation, as compared with the PHBV NPs‐CGN one ( p < 0.05), thus supporting the efficient role of HA in increasing the growth and development of osteoblasts, 44 which could be attributed to the osteoconductive nature of HA. In agreement with our findings, several scientists have also reported the greater viability of osteoblast cells for the scaffolds fabricated with HA 45,46 . Beside these, assessing the results of the viability of cells treated with drug solution and the HPN‐CGN hydrogel showed that the proliferation level of MG‐63 cells on the HPN‐CGN hydrogel was remarkably higher than that of the drug solution, thus confirming the osteoblastic stimulatory effect of both hydrogel material and HPN.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the PHBV NPs‐CGN‐HA hydrogel showed higher efficiency in terms of promoting MG‐63 proliferation, as compared with the PHBV NPs‐CGN one ( p < 0.05), thus supporting the efficient role of HA in increasing the growth and development of osteoblasts, 44 which could be attributed to the osteoconductive nature of HA. In agreement with our findings, several scientists have also reported the greater viability of osteoblast cells for the scaffolds fabricated with HA 45,46 . Beside these, assessing the results of the viability of cells treated with drug solution and the HPN‐CGN hydrogel showed that the proliferation level of MG‐63 cells on the HPN‐CGN hydrogel was remarkably higher than that of the drug solution, thus confirming the osteoblastic stimulatory effect of both hydrogel material and HPN.…”
Section: Resultssupporting
confidence: 92%
“…In agreement with our findings, several scientists have also reported the greater viability of osteoblast cells for the scaffolds fabricated with HA. 45,46 Beside these, assessing the results of the viability of cells treated with drug solution and the HPN-CGN hydrogel…”
Section: Effect Of the Hydrogel Scaffolds On The Viability Of Mg-63 C...mentioning
confidence: 99%
“…This may indicate that the nano-rough surface can improve cell adhesion and growth for bone regeneration. Thus, the higher surface nano-roughness of the nanocomposite may facilitate greater cell adhesion and proliferation in it [25].…”
Section: Characterization Of Samplesmentioning
confidence: 99%
“…Alginate [ 22 ], chitosan [ 23 ], pectin [ 24 ], carboxymethyl cellulose [ 2 ], agarose [ 25 ] and k-carrageenan [ 26 ] are often used for their biological and physical properties that are vital for obtaining suitable scaffolds [ 16 , 27 ]. 3D printed hydrogels made of chitosan and pectin were assessed for lidocaine delivery in wound treatment; the results indicated that these materials represent proper candidates for wound dressings [ 24 ].…”
Section: Introductionmentioning
confidence: 99%